EagleView: A genome assembly viewer for next-generation sequencing technologies - Huang, Weichun; Marth, Gabor (Genome Research, 2008)
The emergence of high-throughput next-generation sequencing technologies (e.g., 454 Life Sciences [Roche], Illumina sequencing [formerly Solexa sequencing]) has dramatically sped up whole-genome de novo sequencing and resequencing. While the low cost of these sequencing technologies provides an unparalleled opportunity for genome-wide polymorphism discovery, the analysis of the new data types and huge data volume poses formidable informatics challenges for base calling, read alignment and genome assembly, polymorphism detection, as well as data visualization. We introduce a new data integration and visualization tool EagleView to facilitate data analyses, visual validation, and hypothesis generation. EagleView can handle a large genome assembly of millions of reads. It supports a compact assembly view, multiple navigation modes, and a pinpoint view of technology-specific trace information. Moreover, EagleView supports viewing coassembly of mixed-type reads from different technologies and supports integrating genome feature annotations into genome assemblies. EagleView has been used in our own lab and by over 100 research labs worldwide for next-generation sequence analyses. The EagleView software is freely available for not-for-profit use at http://bioinformatics.bc.edu/marthlab/EagleView.